HSF1 in macrophages suppressed the progression of asthma via modulating SIRPα/SHP2—Dectin-1/ SYK mediated ROS and inflammatory responses - Xiaojuan Liu; Yingqian Zhang; Huifang Wu; Jingli Zhang; Yingxue Wang; Huifeng Zhang (Scientific Reports)
Abstract HSF1, SIRPα, and Dectin-1 play crucial roles in immune regulation and inflammatory responses, their rols in asthma remained unclear, thereby the study was carried on. Twenty-one SPF-grade C57BL/6 mice were randomly divided into three groups: sham group, Model group, and Model + HSF1A group, with seven mice in each group. Except for the sham group, the other two groups were induced with OVA to establish an asthma model. The Model + HSF1A group was additionally treated with HSF1A. General conditions of the mice were observed. Lung tissue damage was assessed with Masson staining. RAW264.7 cells were divided into NC group, OVA + LPS group, HSF1A + OVA + LPS group, KRIBB11 + OVA + LPS group, SIRPα-OE + KRIBB11 + OVA + LPS group, SIRPα-OE + OVA + LPS group and SIRPα-KD + KRIBB11 + OVA + LPS group. The levels of GSH, MDA, IL-1β and TNFα in serum and cell supernatants were determined by ELISA. Protein expression in lung tissue and RAW264.7 cells was detected by Western blotting. In in vivo experiments, OVA-induced asthmatic mice exhibited severe airway resistance, collagen deposition, and elevated ROS and pro-inflammatory cytokines.HSF1A treatment improved lung function, reduced fibrosis, and restored redox balance. In vitro, HSF1A enhanced SIRPα expression and inhibited SYK/Dectin-1 signaling in LPS/OVA-stimulated macrophages, whereas HSF1 knockdown exacerbated inflammation. overexpression of SIRPα reversed KRIBB11-induced SYK activation, confirming the regulatory role of HSF1. HSF1 in macrophages regulates ROS and inflammatory responses by modulating the SIRPα/Dectin-1/SYK balance, thereby inhibiting the progression of asthma.